Mexican Basic Psychological Need Satisfaction and Frustration Scale in Physical Education - Zamarripa, Jorge; Rodríguez-Medellín, René; Pérez-Garcia, José Alberto; Otero-Saborido, Fernando; Delgado, Maritza (Frontiers in Psychology, 2020)
Basic psychological needs are an energizing state that if satisfied, will produce an increase in confidence and a healthy motivational orientation that leads to wellness. The frustration of these needs is the opposite concept to the satisfaction, which refers to the negative sensation experimented by an individual when he or she perceives that their psychological needs are being actively limited by the actions of other significant. To date, we have not found instruments validated in Spanish that measure both the satisfaction and frustration of basic psychological needs in the physical education context. Therefore, the aims of this study are adapting the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS) to the physical education context in Mexico; examine its psychometric properties, structure and factorial invariance by gender in a sample of fifth and sixth-grade elementary school students. This study included a total of 1,470 fifth and sixth-grade students from elementary schools in the metropolitan area of Monterrey, Nuevo Leon, Mexico participated. The results support the reliability, validity, structure, and strict invariance of the sixth Mexican version of the basic psychological need satisfaction and frustration scale in physical education (BPNSFS-PE). The BPNSFS-PE can be used to measure the satisfaction and/or frustration of the basic psychological need of students in physical education class and to perform comparisons between groups of boys and girls.